1980
DOI: 10.1159/000225484
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Detecting the Carcinogenicity of Bracken Fern Using an Egyptian Toad

Abstract: Neoplasms developed in 18 of 98 toads, Bufo regularis, subjected to enforced feeding with bracken fern. They comprise 7 cases of adenocarcinoma in the ileum, 16 cases of hepatomas in the liver and 6 cases of neoplasms in the kidney due to metastases from the hepatomas. The results demonstrate that the Egyptian toad can be considered as an advantageous model for detecting the carcinogenicity of bracken fern, since the lesions occur faster than in other experimental animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Roe and Field [25] stated that weak tumour promotion was observed with terpentine oil and a-pinene, one of its principle constituents. Many investigators have shown that frogs and toads can be used as models for determining the carcinogenicity of substances [2,[5][6][7]13]. Similarities between the cytologic characteristics of tumours in amphibians and mammals have been noted [2,4], In the present investigation, the Egyptian toad (Bufo regularis) was chosen as a biological test animal to examine the possible carcinogenic effect of black pepper (P. nigrum).…”
Section: Introductionmentioning
confidence: 98%
“…Roe and Field [25] stated that weak tumour promotion was observed with terpentine oil and a-pinene, one of its principle constituents. Many investigators have shown that frogs and toads can be used as models for determining the carcinogenicity of substances [2,[5][6][7]13]. Similarities between the cytologic characteristics of tumours in amphibians and mammals have been noted [2,4], In the present investigation, the Egyptian toad (Bufo regularis) was chosen as a biological test animal to examine the possible carcinogenic effect of black pepper (P. nigrum).…”
Section: Introductionmentioning
confidence: 98%
“…The primary bile acids, cholic acid (CA) and chenodcoxycholic acid, were found to produce an N-methyl-N-nitro-Nnitrosoguanidinc (MNNG)-induced colon tumorpromoting activity in rats [18], Also, feeding of CA increased N-methyl-N-nitrosourea (MNU)-induced colon carcinogenesis in rats [3,4]. On the other hand, amphibian tumors have been studied by several au thors [7,10,26], More recently, it has been reported that chemical carcinogens induced tumor in toads [1, 21 24], It is worth mentioning that similarities in cytological characteristics between tumors in frogs and human beings have been documented [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors recommended the use o f amphibians as quick biological test animals for screening the car cinogenicity o f chemicals [16][17][18][19][20][21] …”
Section: Introductionmentioning
confidence: 99%